2021
DOI: 10.3390/medicina57080827
|View full text |Cite
|
Sign up to set email alerts
|

TACI Mutations in Primary Antibody Deficiencies: A Nationwide Study in Greece

Abstract: Background and objectives: Monoallelic (heterozygous) or biallelic (homozygous or compound heterozygous) TACI mutations have been reported as the most common genetic defects in patients with common variable immunodeficiency (CVID), which is the most common clinically significant primary immunodeficiency in humans. The aim of our study was to evaluate the prevalence and any correlations of TACI defects in Greek patients with primary antibody deficiencies. Materials and Methods: 117 patients (male/female: 53/64)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…One of our study limitations is the fact that we did not have molecular data for the entire cohort of patients (with the exception of the molecular analysis of CTLA4 gene for all and TNFRSF13B/TACI for the great majority of the enrolled patients [33]. Consequently, we have not performed association studies of the genetic background of affected individuals with the phenotype of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…One of our study limitations is the fact that we did not have molecular data for the entire cohort of patients (with the exception of the molecular analysis of CTLA4 gene for all and TNFRSF13B/TACI for the great majority of the enrolled patients [33]. Consequently, we have not performed association studies of the genetic background of affected individuals with the phenotype of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Greece reported that monoallelic defects in TACI may act as susceptibility or disease modifying factor in the pathogenesis of CVID. It was, however, observed that patients with CVID with TACI defects had significantly higher risk of autoimmune cytopenia as compared to patients with CVID without any TACI defect ( 61 ). In addition, studies have shown that TACI plays an important role in central B cell tolerance and defects in TACI lead to impaired central B cell tolerance leading to an increased production of autoreactive B cells ( 62 ).…”
Section: Pathophysiology Of Non-cvid Associated Autoimmune Cytopeniamentioning
confidence: 95%
“…FANCP/SLX4 Fanconi anemia, complementation group P/Structure-Specific endonuclease subunit) Cases 14 and 15 are siblings diagnosed with CVID who carry a pathogenic mutation in TNFRSF13B, which is one of the more common variants found in immune deficiencies 96,97 . The same variant has been found in several other PANS cases (unpublished observations).…”
Section: Fanci (Fanconi Anemia Complementation Group I)mentioning
confidence: 99%